Evaluation of the Quality of Accounting and Analytical Information at the Electrical Enterprises of Perm Region - MUKHINA, Eugeniia Rinatovna; DEPUTATOVA, Ludmila Nikolaevna; POSTNIKOV, Vladimir Pavlovich; STARKOV, Yuriy Valentinovich; MARKOVA, Nina Anatolyevna (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The article describes the role of accounting and analytical information in the control system. Such terms as ‘registration-analytical system’, ‘accounting and analytical support’, ‘accounting and analytical information’ are discussed. Directions, which characterize the terminological field of accounting and analytical system, were formulated in this article. Approaches of different researchers to the definition of ‘registration-analytical system’ were analyzed. The authors’ definition of the ‘registration-analytical system’ category was formulated on the basis of systematization of scientific approaches. Qualitative characteristics of accounting and analytical information were given. Based on the survey, we evaluated the quality of accounting and analytical information at the electrical enterprises of Perm region. The scientific novelty of this work is to develop the theoretical aspects of accounting and analytical system that provide its conceptual representation and the practical adaptation of the fundamental provisions.